The Analysis of the Effect of Corporate Social Responsibility (CSR) on the Financial Performance and HDI of Extractive Companies Listed on the IDX for the Years of 2008-2017 - Sasmito Sudio Usodo; Rini Yayuk Priyati; Iqbal Miftakhul Mujtahid (International Journal of Supply Chain Management, 2021)
Corporate Social Responsibility (CSR) disclosure and financial performances are reported annually by companies whose shares are listed on the Indonesia Stock Exchange. The purpose of this study was to analyze the effect of CSR disclosure on the financial performance of extractive companies listed on the Indonesia Stock Exchange. Moreover, we also examined the effect of those companies’ CSR on the Human Development Index (HDI). Data used in the study were originated from 10 companies' annual reports and financial reports for the years 2008-2017. The analysis method used was simple regressions using panel data. Financial performance was measured by Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). Another variable studied was the Human Development Index (HDI). The results show that CSR has a significant effect on the company’s financial performance and HDI.